Phyllanthus emblica fruit extract alleviates halitosis and reduces the inflammatory response to oral bacteria - Cheng LU; Liu QING; Lu YINA (University of São Paulo, 2024)
Abstract Objective To assess the efficacy of Phyllanthus emblica extract in alleviating halitosis and reducing the inflammatory response to halitosis-related bacteria. Methodology This investigation, using Phyllanthus emblica fruit extract (PE), involved four aspects. First, we evaluated the effect on growth and aggregation of halitosis-related bacteria, including Fusobacterium nucleatum, Porphyromonas gingivalis, and Solobacterium moorei, using a microdilution assay and scanning electron microscopy. Second, volatile sulfur compound (VSC) levels were measured on individuals with halitosis in randomized short-term (26 participants) and double-blind randomized long-term trials (18 participants in each group) after rinsing with PE for 3, 6, and 12 h, and 28 days. Third, we analyzed pro-inflammatory cytokine expression in TR146 cells using quantitative real-time PCR and enzyme-linked immunosorbent assays. Lastly, we assessed pro-inflammatory cytokine secretion and Toll-like receptor (TLR) 2 mRNA expression via the same experimental methods in a three-dimensional oral mucosal epithelial model (3D OMEM). Results PE extract dose-dependently inhibited the growth of F. nucleatum (50% inhibition concentration [IC50]=0.079%), P. gingivalis (IC50=0.65%), and S. moorei (IC50=0.07%) and effectively prevented bacterial aggregation. Furthermore, VSC contents decreased significantly at 3, 6, and 12 h after rinsing with 5% PE compared with those in the control. Long-term use of mouthwash containing 5% PE for 28 days led to a significant decrease in VSC contents. PE attenuated the F. nucleatum- or P. gingivalis-stimulated mRNA expression and protein release of interleukin (IL)-6 and IL-8 in TR146 cells. It also suppressed IL-8 and prostaglandin E2 secretion and TLR2 mRNA expression in F. nucleatum-induced OMEMs. Conclusion Our findings support the use of PE in oral care products to alleviate halitosis and it may reduce inflammation.